Towards prevention of diabetic peripheral neuropathy: clinical presentation, pathogenesis, and new treatments. Issue 10 (October 2022) - Elafros, Melissa A; Andersen, Henning; Bennett, David L; Savelieff, Masha G; Viswanathan, Vijay; Callaghan, Brian C; Feldman, Eva L
Summary: Diabetic peripheral neuropathy (DPN) occurs in up to half of individuals with type 1 or type 2 diabetes. DPN results from the distal-to-proximal loss of peripheral nerve function, leading to physical disability and sometimes pain, with the consequent lowering of quality of life. Early diagnosis improves clinical outcomes, but many patients still develop neuropathy. Hyperglycaemia is a risk factor and glycaemic control prevents DPN development in type 1 diabetes. However, glycaemic control has modest or no benefit in individuals with type 2 diabetes, probably because they usually have comorbidities. Among them, the metabolic syndrome is a major risk factor for DPN. The pathophysiology of DPN is complex, but mechanisms converge on a unifying theme of bioenergetic failure in the peripheral nerves due to their unique anatomy. Current clinical management focuses on controlling diabetes, the metabolic syndrome, and pain, but remains suboptimal for most patients. Thus, research is ongoing to improve early diagnosis and prognosis, to identify molecular mechanisms that could lead to therapeutic targets, and to investigate lifestyle interventions to improve clinical outcomes.